1982
DOI: 10.1073/pnas.79.18.5542
|View full text |Cite
|
Sign up to set email alerts
|

A M r 95,000 polypeptide in Porphyridium cruentum phycobilisomes and thylakoids: Possible function in linkage of phycobilisomes to thylakoids and in energy transfer

Abstract: Two pigmented polypeptides with the same molecular weight (Mr 95,000) were isolated from the photosynthetic apparatus of Porphyridium cruentum by sodium dodecyl sulfate/ polyacrylamide gel electrophoresis. A blue polypeptide from phycobilisomes had absorption and fluorescence emission spectra similar to those of allophycocyanin. A green-pigmented polypeptide from photosynthetic membranes (free of phycobilisomes) contained chlorophyll a. Several properties were common to the Mr 95,000 polypeptides from both sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1
1

Year Published

1985
1985
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(41 citation statements)
references
References 18 publications
(15 reference statements)
0
39
1
1
Order By: Relevance
“…The ApcE protein or "anchor polypeptide" of the phycobilisome core is implicated in the interaction with the membrane (7-9). Proposals for the association of ApcE with the membrane have included an integral membrane domain (7) or a covalently attached acyl group (11). However, we found that cooling below the phase transition temperature of the membrane had no significant effect on the mobility of phycobilisomes (Fig.…”
Section: Mobility Of Phycobilisomes and Photosystem Ii-our Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…The ApcE protein or "anchor polypeptide" of the phycobilisome core is implicated in the interaction with the membrane (7-9). Proposals for the association of ApcE with the membrane have included an integral membrane domain (7) or a covalently attached acyl group (11). However, we found that cooling below the phase transition temperature of the membrane had no significant effect on the mobility of phycobilisomes (Fig.…”
Section: Mobility Of Phycobilisomes and Photosystem Ii-our Resultsmentioning
confidence: 78%
“…Phycobilisomes are largely composed of hydrophilic protein subunits (1,2). The ApcE protein, a high molecular weight component of the phycobilisome core, seems to play a crucial role in phycobilisome-membrane association (7,8). However, sequence analysis did not reveal any likely membrane-spanning domain (9), although phase partitioning suggests a hydrophobic region on the protein (10).…”
mentioning
confidence: 99%
“…Linkers in core and rods (Lc and LR, respectively) ensure stability of disks (Glazer, 1985). Attachment of PBS on thylakoids (Redlinger and Gantt, 1982) and stability of the core are attributed to a (Isono and Katoh, 1987;Capuano et al, 1993).…”
Section: ~ ~ ~mentioning
confidence: 99%
“…The interactions of the biliproteins with the nonpigmented linker polypeptides (47) cause minor shifts in the spectral properties of the associated chromophores and may increase the efficiency of energy transfer between hexamers (18)(19)(20). Moreover, specific phycobiliproteins in the core of the phycobilisome (35,36,44) serve as energy bridges between the AP and the reaction center Chl of PSII (18,38,39).…”
Section: Abstracrmentioning
confidence: 99%